Molecular structures of flavonoid co-formers for cocrystallization with carbamazepine - Lee, Cheong Cheon; Hee Lim, Ju; Young Cho, A.; Yoon, Woojin; Yun, Hoseop; Won Kang, Jeong; Lee, Jonghwi (Journal of Industrial and Engineering Chemistry, 2023)
Flavonoids have numerous beneficial effects on human health, such as antioxidant capacity and immune-boosting effects, which make them attractive cocrystal formers for drugs. Previously, a co-crystal between carbamazepine (CBZ) and naringenin, a flavonoid, was discovered, but no understanding on the requirements of cocrystal formers was assessed. Herein, the structural requirement of flavonoids cocrystallization with CBZ was examined using eight different natural flavonoids with planar and bent structures and 0–4 phenolic groups including the naringenin. The flavonoids without double bonds in their heterocyclic rings (F1, P2, and N3) formed cocrystals with monoclinic unit cells and a 1:1 CBZ to flavonoid molecular ratio, whereas the flavonoids with double bonds (F1d, C2d, and A3d) did not form cocrystals. F1, P2, and N3 had geometrically bent structures, which enabled the formation of cocrystals. The phenolic groups of flavonoids play an essential role in cocrystal formation with CBZ, undergoing strong intermolecular interactions. The flavonoid with no phenolic group, F0, could not form a cocrystal. For CF1, CP2, and CN3, the melting temperature, packing coefficient, and hydrogen bonding energy of the cocrystals increased as the number of phenolic groups increased. These results confirm that the phenolic groups and molecular geometry of flavonoids are critical cocrystal forming factors.
Keywords: Bend structure; Carbamazepine; Co-crystallizations; Co-crystals; Flavonoid; Naringenin; Pharmaceutical cocrystal; Phenolic groups; Polyphenols; Antioxidant; Cocrystal; Flavonoid; Pharmaceutical cocrystal; Polyphenol